2020
DOI: 10.1007/s00784-020-03716-4
|View full text |Cite
|
Sign up to set email alerts
|

Is MRI a viable alternative to CT/CBCT to identify the course of the inferior alveolar nerve in relation to the roots of the third molars?

Abstract: Objectives To assess the reliability of judging the spatial relation between the inferior alveolar nerve (IAN) and mandibular third molar (MTM) based on MRI or CT/CBCT images. Methods Altogether, CT/CBCT and MRI images of 87 MTMs were examined twice by 3 examiners with different degrees of experience. The course of the IAN in relation to the MTM, the presence/absence of a direct contact between IAN and MTM, and the presence of accessory IAN were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It was necessary to correct the fusion manually through trial and error to allow the best possible evaluation. Therefore, we can only confirm the need for a perfect automatic fusion algorithm from other studies [ 23 ]. However, compared to the MRI protocols used in other studies, we achieved a much better image quality and more accurate evaluation using 3D-DESS MRI protocol.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…It was necessary to correct the fusion manually through trial and error to allow the best possible evaluation. Therefore, we can only confirm the need for a perfect automatic fusion algorithm from other studies [ 23 ]. However, compared to the MRI protocols used in other studies, we achieved a much better image quality and more accurate evaluation using 3D-DESS MRI protocol.…”
Section: Discussionmentioning
confidence: 81%
“…This study confirms the trends observed by Deepho et al that there is a tendency for the “small pattern” (21%) to be more prevalent in the retromolar region. Nevertheless, it should be noted that the “same pattern” was most frequent in the retromolar (72%) and molar (76%) regions [ 23 ]. The large pattern was observed in only 7% of the cases, which is most likely explained by insufficient fusion or insufficient MRI image quality due to motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations